Knowledge Transfer of IoT Utilization and Benefits for Primary School Pupils in Remote Rural Area (S/O 21347) - Mansor, Nur Suhaili; Awang, Hapini (UUM, 2023)
This research project seeks to investigate the current level of knowledge about IoT among primary school students in remote rural areas, as well as to implement an IoT knowledge transfer program to improve their understanding. The project is motivated by the desire to bridge the digital divide and improve digital education in indigenous communities. In the long run, a lack of awareness about IoT and its benefits may widen the gap between rural and urban communities. Indigenous communities frequently settle in remote rural areas, where they face a number of challenges, including a lack of proper facilities and isolation. This problem is widespread throughout the world, including in developing countries such as Malaysia, the United States, and Australia. The technological divide between rural and urban areas has long been an issue, and governments around the world have implemented several initiatives to address it, including the Sustainable Development Goals (SDG). Although digital education has been implemented in rural schools, the quality of education received by the indigenous community in remote rural areas is frequently inferior to that received by urban communities. This is because the indigenous community lives in rural areas that are remote and lack proper facilities. As a result, the indigenous community lags behind in terms of ICT knowledge and awareness, particularly in the area of IoT. The study intends to investigate indigenous youth perspectives on IoT as well as the potential of IoT to improve the quality of digital education in remote rural areas. The findings could help to improve awareness of IoT and the quality of digital education for indigenous communities in remote rural areas. This, in turn, could help to bridge the digital divide and improve indigenous communities' access to digital education. Finally, this research project aims to address the issue of IoT awareness and knowledge among primary school students in remote rural areas. The indigenous community's future may be jeopardized due to a lack of understanding about IoT and its benefits. The findings of this study could help to improve digital education and bridge the digital divide, ultimately benefiting the indigenous community in remote rural areas.